THE ROLE OF INDIVIDUAL STYLE IN SHAPING LITERARY TRADITION - Ochilxonov Abdujalolxon Davron o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The present study examines the role of individual style in shaping and transforming literary tradition within the framework of modern literary theory and stylistics. Traditionally, literary tradition has been perceived as a stable body of inherited forms, themes, and conventions; however, contemporary approaches emphasize its dynamic and evolving nature. Within this process, individual style emerges as a crucial force that not only reflects personal creativity but also contributes to the renewal and reinterpretation of tradition. The relevance of the research lies in the growing scholarly interest in the interaction between authorial innovation and cultural continuity. The aim of this study is to explore how individual style functions as an agent of change within literary tradition, to analyze the mechanisms through which writers influence and reshape established norms, and to highlight the interdependence of tradition and individuality. The research employs descriptive, analytical, and interpretative methods. The findings demonstrate that literary tradition is not merely preserved but actively constructed through the creative contributions of individual authors.